Pengaruh Gaya Kepemimpinan Terhadap Kepuasan Kerja Sebagai Variabel Mediasi Di CFC Sumatera Utara - Ayu Ayu Priyanti; H. M Hermansyur; Aulia Arief Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This research aims to determine the effect of leadership style organizational culture on employee performance with job satisfaction as a mediating variable at PT. Pioneerindo Gourmet International (CFC) at North Sumatra. The results of the picture above can be explained for the first path that Leadership Style (X1) has an effect on Job Satisfaction (Z) with a Standardized Coeffciients Beta value of 0.139, meaning that for every 1% addition of Leadership Style, it will increase Job Satisfaction by 13.9%%. with an R2value of 0.664, it means that for every addition of 1%, Job Satisfaction will increase Job Satisfaction (Z) by 66.4%. Organizational Culture (X2) has an effect on job satisfaction (Z) with a Standardized Coeffciients Beta value of 0.561, meaning that for every 1% addition of Organizational Culture, it will increase Job Satisfaction by 56.1%. with an R value of 0.664, it means that for every addition of 1%, Job Satisfaction will increase Job Satisfaction (Z) by 66.4%.